The PELATIHAN PEMBUATAN MEDIA PEMBELAJARAN ANIMASI SEDERHANA MENGGUNAKAN CANVA PADA TK LABORATORIUM UM - Mustikasari, Bunga Fefiana; Rini, Denik Ristya; Wardani, Nuril Kusuma; Sillah, Sumardianshah Bin (Jurnal Al Maesarah, 2026)
The integration of technology-based instructional media has become essential to enhance the quality of early childhood education. However, many kindergarten teachers still face limitations in developing digital animated learning media. This community service program aimed to strengthen the pedagogical and digital competencies of kindergarten teachers at the UM Laboratory Kindergarten through training on creating simple animated learning media using Canva. The program employed a participatory training approach consisting of three stages: conceptual socialization of digital learning media, hands-on practice in animation development, and evaluation through knowledge tests and product-based assessment. The participants comprised 20 kindergarten teachers who completed the entire training program. The results demonstrated a significant improvement in teachers’ knowledge, technical skills, and self-confidence in utilizing Canva to design animated learning media aligned with early childhood developmental characteristics. All participants successfully produced simple animated instructional media suitable for classroom implementation. These findings indicate that practice-oriented technology training using user-friendly digital platforms is an effective strategy for enhancing teachers’ pedagogical competence and digital literacy in early childhood education, particularly in responding to the demands of 21st-century learning.